2017
DOI: 10.1371/journal.pone.0174540
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health behaviors of female sex workers in Dhaka, Bangladesh

Abstract: ObjectivesThe objective of this study was to document sexual and reproductive health (SRH) practices among female sex workers (FSWs) including abortion, pregnancy, use of maternal healthcare services and sexually transmitted infections (STIs) with the aim of developing recommendations for action.MethodsA total of 731 FSWs aged between 15 and 49 years were surveyed using a stratified sampling in Dhaka, Bangladesh. A workshop with 23 participants consisted of policy makers, researchers, program implementers was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 33 publications
1
40
1
1
Order By: Relevance
“…Consequently, FSWs resorted to concealing their job status and this complicated the provision of appropriate comprehensive services [53]. From other studies, FSWs alluded to providers delivering services in a hateful manner after disclosure of job status [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, FSWs resorted to concealing their job status and this complicated the provision of appropriate comprehensive services [53]. From other studies, FSWs alluded to providers delivering services in a hateful manner after disclosure of job status [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The FSW showed a high level of knowledge about the purpose and benefits of the test, but few recognized the need for routine testing, the potential health benefits of testing, and the need to protect their sexual partners. Studies have reported an increase in FSW testing when self-perceived risks associated with sex work increase, such as denial of condoms by clients, forced sex due to lack of condoms, condom failure, use of psychoactive substances, among others 1 , 3 , 6 , 18 - 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The fear of being discriminated against if the test is HIV-positive is also an important barrier to testing 1 , 2 , 5 , 16 . Situations of stigma and social exclusion resulting from socioeconomic status, profession, race, among others, seem to contribute to distancing FSW from the health system, reducing the chance of access to early diagnosis for HIV 2 , 5 , 6 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the experience of pregnancy (n=61), only 27.7% of the women attended four or more prenatal consultations and over half of them did not attend any post-natal follow-up. 4 These experiences are an alert, especially in contexts of high rates of HIV and sexually transmitted infections (STIs), being essential to adapt services to meet these needs, reinforcing that the gaze should not be directed only to those situations of pre-availability, but to health care as a whole, respecting the dignity of every woman. 4 Another study revealed that pregnancy for female sex workers is a possibility to earn respect as mothers, in order to avoid the stigma that rests upon them and to solidify relationships with their partners, sometimes representing risks to the health of the couple.…”
mentioning
confidence: 99%
“…4 These experiences are an alert, especially in contexts of high rates of HIV and sexually transmitted infections (STIs), being essential to adapt services to meet these needs, reinforcing that the gaze should not be directed only to those situations of pre-availability, but to health care as a whole, respecting the dignity of every woman. 4 Another study revealed that pregnancy for female sex workers is a possibility to earn respect as mothers, in order to avoid the stigma that rests upon them and to solidify relationships with their partners, sometimes representing risks to the health of the couple. 5 This study also emphasized that pregnant sex workers generally sought services of prenatal care, but rarely revealed their occupation, hindering the planning and implementation of actions directed to to their needs.…”
mentioning
confidence: 99%